Introduction to Neuroscience - Hedges, Valerie (Open textbook library., 2022)
Introduction to Neuroscience is designed for undergraduate students enrolled in introductory neuroscience courses. This book specifically targets students enrolled in Introduction to Neuroscience 1 and Introduction to Neuroscience 2 at Michigan State University and primarily contains topics covered in those courses. This first edition will guide students through the structure and function of nervous system cells and nervous system structures, signaling within the nervous system, and introduce various sensory systems. A future edition that will be completed in spring 2023 will include the somatosensory system, motor systems, motivation and reward, stress, sex and the brain, emotions, nervous system disorders, learning, and memory. This text has been remixed and revised from two different open educational resources aimed at undergraduate neuroscience students: Foundations of Neuroscience by Casey Henley, Michigan State University The Open Neuroscience Initiative by Austin Lim, DePaul University In addition, new original content has been added to supplement what was provided in the above texts. The text includes many images and animations throughout and will be divided into shorter chapters that focus on a single topic. As this text is meant for undergraduate students, the writing is aimed at students that have not taken a neuroscience course before. Neuroscience terminology will be defined throughout the text through the use of the embedded Glossary terms to help with ease of reading. Additionally, important terms are bolded. Each chapter will end with an interactive quiz for student self-evaluation of the content. Find errors or have suggestions? Please email hedgesva@msu.edu